No One Can Hide: Indian Public Sector Banks’ Performance Evaluation Through OBSI: A Re- Fe Panel Approach - Gurjar, Hariom (International Journal of Engineering and Management Research, 2026)
In recent years, increased competition, regulatory reform laws, new financial market breakthroughs, lower deposit earnings and the purchase of funds for subsequent financial intermediary in contingent assets and liabilities, and the rapid growth and dissemination of new technologies have all prompted banks to enter the new OBSI arena. To assess the impact of these OBSI in the performance of the large public bank in India for a decade, we used multiple regression models with a proper test of model fit and robustness. We used three main performance parameter risk, profitability and leverage to regress within multidimensional with the set of OBS items. We found mix impact of OBSI in the performance of these large banks as all factors of risk and liquidity were insignificant but ROE as a major factor of profitability was found significant role in the performance.